PERAN KEPEMIMPINAN DALAM MEMBANGUN BUDAYA ORGANISASI YANG EFEKTIF UNTUK MENINGKATKAN KINERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH DI PROVINSI RIAU - Indrawansyah, Indrawansyah; Marnis, Marnis (Jurnal Tepak Manajemen Bisnis, 2017)
The purpose of this research is for determining the effect of leadership,organizational culture toward staff performance at the regional disaster managementagency in Riau province. The variables used in this research are leadership andorganizational culture as independent variables and organizational performance as adependent variables.The sampling method used is stratified random sampling method with samples of 79 ofthe 371 person working at the regional disaster management agency in Riau provinceperiod of 2015. Statistical analysis used to examine the effects of leadership andorganizational culture toward organizational performance is path analysis which canexplain the relationship between variables either directly or indirectly.The results of this study indicate that leadership has a direct effect towardorganizational culture, but hasnât a direct effect toward organizational performance.Organizational culture has a direct effect toward organizational performance.Leadership has an indirect effect toward organizational performance throughorganizational culture.